PERANCANGAN SISTEM PENUNJANG KEPUTUSAN PEMERINGKATAN DAN STRATEGIPENGEMBANGAN KELOMPOK TANI KAKAO DI INDONESIA (Jurnal Inovisi (Teknik Industri), 2019)
AbstractThere have been many programs launched by the government to develop farmer groups (Poktan). Either by the ministry of agriculture or by other technical ministries. The effectiveness of various programs that have been carried out needs to be evaluated by farmer groups. This paper evaluates the effectiveness of the assistance using Quality Functional Deployment (QFD). An evaluation was carried out for the program from 2011 to 2016. The strategy for developing farmer groups was carried out using a prospective analysis. The results of the evaluation will be used as improvements for the development of farmer group programs in the future. From the results of the evaluation, leadership development in groups is something that needs to be improved. Dominant factors that will influence the successful development of agricultural product processing groups in Indonesia, namely: (1) government policies, (2) financial administration and governance assistance, (3) growing entrepreneurship, (4) institutional strengthening, (5) special program credits, and (6) Access to funding institutions. Keywords: farmers group, QFD, prospective analysis AbstrakTelah banyak program yang diluncurkan pemerintah untuk mengembangkan kelompok tani (Poktan). Baik oleh kementerian pertanian atau oleh kementerian teknis lainnya. Berbagai program yang telah dilakukan perlu dievaluasi efektivitasnya kepada kelompok tani. Makalah ini mengevaluasi keefektifan bantuan tersebut dengan menggunakan Quality Functional Deployment (QFD). Evaluasi dilakukan untuk program dari 2011 hingga 2016. Strategi pengembangan kelompok tani dilakukan dengan analisis prospektif. Hasil evaluasi akan digunakan sebagai penyempurnaan untuk pengembangan program kelompok tani di masa depan. Dari hasil evaluasi, pengembangan leadership dalam kelompok merupakan hal yang perlu ditingkatkan.Faktor-faktor dominan yang akan mempengaruhi keberhasilan pengembangan kelompok pengolahan hasil pertanian di Indonesia yaitu : (1) kebijakan pemerintah, (2) bantuan dan bimbingan administrasi dan tata kelola keuangan, (3) penumbuhan entrepreneurship, (4) penguatan kelembagaan, (5) kredit program khusus, dan (6) Akses ke lembaga dana. Kata kunci: kelompok tani, QFD, analisis prospektif